Chemotaxonomic comparison of the seed ferns Odontopteris cantabrica and Odontopteris schlotheimii, Middle Pennsylvanian Sydney Coalfield, Canada - D`angelo, José Alejandro (2022)
We present the first comparative spectrochemical data in the study history of Odontopteris schlotheimii Brongniart, 1828–1831 and Odontopteris cantabrica Wagner, 1969. These fossils co-occur in the shaley roof of the Lloyd Cove seam (Ro% = 0.65; Sydney Coalfield, Canada). Fourier transform-infrared spectra show that the sampled pinnules of both species are preserved as fossilized-cuticles. They are prominently aliphatic with distinct methylene and methyl peaks (at 2922 cm–1 and 2852 cm–1); with relatively high contents of carbonyl groups (peaks at 1700 cm–1) that indicate a high degree of molecular cross linking; and with smaller amounts of aromatics (peaks at 820 cm–1 and 750 cm–1) with a low condensation degree of benzene rings. No differences among respective pinnules are inferred from the 3D chemometric model and associate significance tests by the analysis of variance (α = 0.05). At the same time, this method provides new, chemical parameters that, in conjunction with morphological features, could be used to efficiently distinguish species.